Bibliometric insights into metal-organic frameworks modified with metal-based materials for hydrogen storage: Prospects, opportunities and challenges - Abdulkadir, B. A.; Herma Dina, Setiabudi (Elsevier Ltd, 2025)
Backgrounds: Solid-state hydrogen storage technology is known for its reliability and cost-effectiveness. Porous materials such as metal-organic frameworks (MOFs) are a major area of interest because of their high surface area and porosity. Recent advancements in modifying MOFs with metal-based materials offer new avenues for enhancing their storage capacity and stability. However, the research landscape in this area remains complex, necessitating a comprehensive overview.